Analysis of Sharia Hotel Management in Bandung City in the Perspective of Maqashid Syari'ah - Enden Haetami (International Journal of Science and Society, 2021)
This study aims to analyze the management of Sharia hotels in the city of Bandung from the perspective of Maqashid Syari'ah. This research uses qualitative research with a descriptive analysis approach. The data in this study are primary data and secondary data. Methods of data collection in this study are through observation, in-depth interviews, and literature study. This object needs to be studied to find out the ideal Islamic muamalah in the hotel business labeled shari'ah. The population in this study were all hotels marked shari'ah in the city of Bandung. At the same time, the sample in this study is Noor Hotel which is considered a good representation of information and management. With the reflection of Maqasid Al-Syariah, it is hoped that sharia brands can positively influence the sharia-based muamalah format in Indonesia. Based on the research analysis results, it can be concluded that: 1) Material Characteristics, by applying according to Islamic law, namely by checking the identity of visitors carefully and the message service facilities are not the same as Conventional Hotels. The implementation of the sharia management system at the Syariah Hotel Noor Bandung has similarities and differences with other hotels; and 2) Immaterial Characteristics, namely by referring to Maqashid-Shari'ah values, such as Amar Ma'ruf Nahi Munkar, the principle of upholding the truth, the focus of supporting justice, the principle of Latuzlimuna wala Tuzlamuna, the principle of trust, and the principle of benefiting the ummah.